Genotype Distribution Pattern, Subgenotipe and Subtipe of Hepatitis Virus B in Generalpopulation from Six Munipios in Timor-Leste - Da Silva H (Journal of Global Pharma Technology, 2018)
Hepatitis B virus infection (HBV) remains a serious health problem in Timor Leste, but data on its prevalence is still very limited. According to some reports, the prevalence of HBsAg in the general population in Timor-Leste ranges from 6.9% - 8.1%. Previous research on blood donors in the city of Dili also indicated the biodiversity of the HBV genotype and HBsAg subtype. This study aims to determine the distribution patterns of genotypes, subgenotypes and subtypes of HBV in the general population in six municipios present in Timor-Leste. This study was conducted using a Cut Lintang design to find out, genotype distribution pattern, subgenotype and HBV subtype. HBsAg examination is done by immunochromatography method. Determination of genotype, subgenotype and HBV subtype was done by analysis of nucleotide sequence of S. gene. The results of 683 subjects from six Munisipio in Timor Leste obtained 69 positive HBsAg. From 69 samples of HBsAg tested positive, genotype C predominant (72,8%), followed by genotype B (25,7%) and genotype A (1,5%). From the subgenotype A1, B3, B7, C1, C2, C7 and C10 there were 3 dominant subgenotypes, subgenotipe C2 (25,8%), followed by subgenotipe C10 (19,7%) and B3 subgenotype (16 , 6). All the major subtypes of HBsAg were found in Timor-Leste, subtype adr (71.2%), followed by ayw subtype (24.2%), adw subtype (3.1%) and ayr subtype (1.5%). Conclusions from this study were three genotypes of HBsAg in the general population of 6 municipios present in Timor-Leste ie genotypes A, B, and C, Subgenotypes A1, B3, B7, C1, C2, C7 and C10, subtype adr, adw, ayw ayr. Genotype C, subgenotype C2, C10 and B3 and subtype adr are the most common genotypes, subgenies and subtypes found in the general population at 6 Municipio in Timor-Leste.Keywords: Genotype, Subgenotype, Hepatitis B Virus Subtype, Timor-Leste.